2020
DOI: 10.1001/jamanetworkopen.2020.25591
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Mental Health Disorders Among University Students in France Confined During the COVID-19 Pandemic

Abstract: Key Points Question What is the mental health state of university students in France who were confined during the coronavirus disease 2019 (COVID-19) pandemic, and what factors are associated with the development of mental health symptoms? Findings This survey study of 69 054 students who experienced quarantine found high prevalence rates of severe self-reported mental health symptoms. Among risk factors identified, female or nonbinary gender, problems with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

80
564
12
53

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 601 publications
(709 citation statements)
references
References 28 publications
80
564
12
53
Order By: Relevance
“…In the present study, female gender was associated with a higher risk of reporting depressive symptoms, which is in line with a large body of previous findings [ 24 , 25 , 26 , 27 , 30 , 31 , 32 , 33 , 34 ]. Moreover, students with a migration background, i.e., double citizens and foreign nationals, and students from families with lower socioeconomic status were more likely to have depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, female gender was associated with a higher risk of reporting depressive symptoms, which is in line with a large body of previous findings [ 24 , 25 , 26 , 27 , 30 , 31 , 32 , 33 , 34 ]. Moreover, students with a migration background, i.e., double citizens and foreign nationals, and students from families with lower socioeconomic status were more likely to have depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to psychosocial factors, students with poor social support, low resilience, and low self-efficacy were more likely to report depressive symptoms. Previous studies of French and Chinese students and adolescents during the pandemic found similar associations between weak feelings of social integration and mental health symptoms [ 33 ], low levels of resilience [ 24 , 35 ], and negative coping [ 35 ], which were risk factors for depressive symptoms. Similarly, pre-pandemic studies of Iranian students, Chinese adolescents, and Chinese athletes showed that low self-efficacy was a risk factor for depressive symptoms [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 70%
“…In a literature study, it was found that in addition to the general population experiencing significant psychological problems, depression, anxiety, and stress increased, especially among healthcare workers, students, service sector workers, women, those in quarantine, and those exposed to misinformation [ 72 ]. The current study found that COVID-19 fear raises individuals’ depression, anxiety, and stress levels above the accepted level, consistent with many other studies [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…In another study conducted with 3524 participants, it was seen that individuals between the ages of 18–33 had more severe symptoms of depression, anxiety, and stress during the COVID-19 pandemic; it has been found that older people generally give better psychological responses [ 45 ]. A study conducted with students during the COVID-19 period in France found that 24.7% of students had high perceived stress, 16.1% depression, and 27.5% anxiety [ 46 ]. In a study conducted on Chinese adolescents (aged 12–18, n = 8079), it was found that 37% of the adolescents had anxiety and 43% had depression, with women being the highest risk group [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on students conducted in France, Ethiopia, China, and Malaysia also point at a high negative impact on college students’ psychosocial health during the COVID-19 pandemic [ 22 , 23 , 24 ]. A study of college students in China found that the prevalence of post-traumatic stress disorder and depression rose to 2.7% and 9.0% during the COVID-19 pandemic [ 25 ].…”
Section: Introductionmentioning
confidence: 99%